2017
DOI: 10.1016/j.pmedr.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Process evaluation of a culturally-tailored physical activity intervention in African-American mother-daughter dyads

Abstract: The purpose of this study was to describe process evaluation data including intervention fidelity, dosage, quality, participant responsiveness, and program reach for the Mothers And dauGhters daNcing togEther Trial (MAGNET) in Springfield, MA, in Spring 2013 and 2014. Seventy-six mother-daughter dyads were randomized to the mother-daughter group (CH-M, n = 28), the child-only group (CH, n = 25), or the health education group (CON, n = 23). CH-M consisted of 60 min of moderate-to-vigorous culturally-tailored da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…“A lower dose of physical attendance was delivered than initially intended due to low attendance rates… one of the major barriers to attending the present intervention was transportation to the intervention site” (Burkart et al., 2017 , p. 91)…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…“A lower dose of physical attendance was delivered than initially intended due to low attendance rates… one of the major barriers to attending the present intervention was transportation to the intervention site” (Burkart et al., 2017 , p. 91)…”
Section: Methodsmentioning
confidence: 99%
“…Studies gave several reasons for low attendance and high attrition rates of participants. Most participants came from underserved populations with low incomes and had limited access to transportation, inhibiting their ability to attend intervention sites (Burkart et al, 2017;Im et al 2018). Bernard-Davila et al, 2015) and Burkart et al (2017) demonstrated that sustained interventions created a burden on participants who had to work for their living.…”
Section: Low Attention and Retention Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed information of study process evaluation procedures and data are reported elsewhere ( Burkart et al, 2017 ). Study process evaluation was assessed during each intervention day by trained staff using a semi-structured questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Aunque los resultados del estudio presentan muy pocas evidencias sobre estrategias desarrolladas en este contexto, las que fueron objeto de análisis permiten evidenciar estrategias efectivas provenientes, por ejemplo, de la enfermería familiar, la cual representa una estrategia para la atención directa a las familias, otorgando educación para la salud de forma personalizada y buscando conocer el funcionamiento familiar para promover la salud (19). En contraste, un estudio realizado con diadas madre-hija, con fundamento en la teoría cognitiva social (SCT) ha sugerido que el comportamiento se aprende, en parte, a través del modelado y la observación de compañeros y modelos de conducta; al respecto, el papel de la madre es fundamental en la promoción de estilos de vida, esto se considera así ya que la madre es la principal encargada de la alimentación de la familia (34,62); de igual forma, los talleres y actividades permanentes con los padres de familia facilitan el modelo de conducta para la conformación de hábitos saludables en los niños (34). Con todo esto, la promoción de la salud es necesaria porque actúa de forma sistemática y participativa con los integrantes de la familia conllevando beneficios directos sobre su salud.…”
Section: Estrategias Orientadas Al Contexto De Familiaunclassified